ADHD symptoms in neurometabolic diseases: Underlying mechanisms and clinical implications. (January 2022) - Cannon Homaei, Selina; Barone, Helene; Kleppe, Rune; Betari, Nibal; Reif, Andreas; Haavik, Jan
Highlights: ADHD symptoms are common in many neurometabolic diseases (NMDs). Many NMDs affect amino acid, neurotransmitter and energy homeostasis in the brain. Mechanisms involved in NMD-related ADHD symptoms may be relevant to understand ADHD symptoms more generally. The detection and treatment of ADHD symptoms in NMDs may be challenging and require particular attention. Abstract: Neurometabolic diseases (NMDs) are typically caused by genetic abnormalities affecting enzyme functions, which in turn interfere with normal development and activity of the nervous system. Although the individual disorders are rare, NMDs are collectively relatively common and often lead to lifelong difficulties and high societal costs. Neuropsychiatric manifestations, including ADHD symptoms, are prominent in many NMDs, also when the primary biochemical defect originates in cells and tissues outside the nervous system. ADHD symptoms have been described in phenylketonuria, tyrosinemias, alkaptonuria, succinic semialdehyde dehydrogenase deficiency, X-linked ichthyosis, maple syrup urine disease, and several mitochondrial disorders, but are probably present in many other NMDs and may pose diagnostic and therapeutic challenges. Here we review current literature linking NMDs with ADHD symptoms. We cite emerging evidence that many NMDs converge on common neurochemical mechanisms that interfere with monoamine neurotransmitter synthesis, transport, metabolism, or receptor functions, mechanisms that are also considered central in ADHD pathophysiology and treatment. Finally, we discuss the therapeutic implications of these findings and propose a path forward to increase our understanding of these relationships.